SUBC'r May Activity Repor (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Activity report for the month of May. Discusses the actions of Urban Resources Inc. on behalf of the tobacco industry. Includes meetings with labor unions regarding clean indoor air, taxes and smoking regulations.